Heat-resistant precoated sand and preparation process thereof

A heat-resistant coated sand formulation using silica sand, anhydrous borax, and boric acid addresses high-temperature casting issues by forming a dense glass layer, enhancing sintering and preventing core deformation, suitable for large-scale complex castings.

CN119159038APending Publication Date: 2024-12-20HEFEI RENCHUANG CASTING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411213688.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing coated sands fail to withstand high temperatures during casting, leading to issues like rapid binder decomposition, shrinkage, surface wrinkles, and mechanical sand sticking due to thermal expansion of silica sand, which compromises the quality of castings.

Method used

A heat-resistant coated sand formulation using silica sand, anhydrous borax, boric acid, phenolic resin, and a curing agent, with specific mass ratios and preparation methods to enhance heat resistance and reduce thermal expansion, forming a dense glass layer that resists molten metal invasion and maintains core structure.

Benefits of technology

The solution provides excellent heat resistance, preventing core deformation and metal penetration, improving sintering rates, and eliminating the need for additional lubricants, suitable for large-scale complex castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119159038A_ABST
    Figure CN119159038A_ABST
Patent Text Reader

Abstract

The invention provides heat-resistant precoated sand and a preparation process thereof, and belongs to the technical field of casting materials. The heat-resistant precoated sand is composed of silica sand, anhydrous borax, boric acid, phenolic resin and a curing agent. The mass ratio of the silica sand to the anhydrous borax to the boric acid is (80-90): (10-20): (0.1-0.5), and the mass of the phenolic resin accounts for 2%-4% of the mass of the silica sand; and the mass of the curing agent accounts for 12-15% of the mass of the phenolic resin. Silica sand and anhydrous borax are used as aggregates, the surfaces of the aggregates are coated with phenolic resin and cured, then boric acid is added, and the heat-resistant precoated sand is obtained. By means of the method, the heat resistance of the precoated sand is remarkably improved, and a lubricating agent does not need to be added; and sand burning and deformation of the casting can be avoided, and the manufacturing cost of the heat-resistant precoated sand is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of casting materials, in particular to the technical field of coated sand, and specifically to heat-resistant coated sand and a preparation process thereof. Background Art

[0002] With the development of my country's automobile, shipbuilding, high-speed rail, aerospace and other technical fields, the use of castings is increasing, and the quality requirements for castings are getting higher and higher. Therefore, the quality requirements for coated sand used in castings are also getting higher and higher. The pouring temperature of steel castings can reach 1600℃, which has exceeded the refractory temperature of silica sand. These castings will release a lot of latent heat when solidifying, causing the binder phenolic resin to burn and decompose rapidly, resulting in shrinkage inside the castings and wrinkles on the surface of the castings. At the same time, the main component of silica sand, SiO2, will undergo thermal phase change expansion at 573℃, causing the sand core mold to crack or the sand core surface to be loose, and the metal liquid will penetrate the sand core, which will lead to mechanical sand sticking. Therefore, improving the heat resistance of coated sand is one of the key factors to ensure the quality of castings. Summary of the invention

[0003] Based on the above problems, the present invention provides a heat-resistant coated sand and a preparation method thereof. The heat-resistant coated sand is added with anhydrous borax and boric acid, and no lubricant is required. The heat-resistant coated sand has good heat resistance and low production cost, and is suitable for producing large-scale iron castings or / and steel castings with complex structures.

[0004] Specifically, the present invention adopts the following technical solutions to achieve the above objectives:

[0005] A heat-resistant coated sand consists of silica sand, anhydrous borax, boric acid, phenolic resin and a curing agent; the mass ratio of the silica sand, the anhydrous borax and the boric acid is (80-90):(10-20):(0.1-0.5), the mass of the phenolic resin accounts for 2%-4% of the mass of the silica sand; the mass of the curing agent accounts for 12%-15% of the mass of the phenolic resin.

[0006] Anhydrous borax is a white crystal or glass, and its α-orthorhombic crystal melting point is 742.5°C, and the β-orthorhombic crystal melting point is 664°C. In the present invention, it can promote the melting of SiO2 and reduce phase change expansion. Boric acid is a white crystalline powder, and in the present invention, it is coated on the surface of sand particles to promote the melting of SiO2 and control thermal expansion. When silica sand is heated, SiO2 undergoes α→β phase change expansion at 573°C. Adding borax can reduce the influence of this expansion force on the sand core, avoiding the sand core from being cracked due to stress and causing metal liquid invasion; at the same time, borax has the same fluxing effect as boric acid, making the sintering of the silica sand skeleton more thorough and firm.

[0007] In a preferred embodiment, the mass ratio of the silica sand, the anhydrous borax and the boric acid is 84:15.7:0.3.

[0008] In a preferred embodiment, the sieve number of the silica sand is 20-270 meshes.

[0009] In a preferred embodiment, the sieve size of the anhydrous borax is 20-270 meshes.

[0010] In a preferred embodiment, the sieve size of the boric acid is 300-500 meshes.

[0011] In a preferred embodiment, the curing agent is hexamethylenetetramine.

[0012] The present invention also provides a method for preparing the heat-resistant coated sand according to any one of the above schemes, comprising the following steps:

[0013] S1. Mixing silica sand and anhydrous borax in proportion to obtain a mixture A; heating the mixture A;

[0014] S2, adding phenolic resin to the heated mixture A and mixing well;

[0015] S3, adding an aqueous solution of a curing agent to the product of step S2 and mixing evenly;

[0016] S4. Add boric acid to the product of step S3 and mix well to obtain the heat-resistant coated sand.

[0017] In a preferred embodiment, in step S1, the mixture A is heated to 140-160°C.

[0018] In a preferred embodiment, the mixture is mixed uniformly by stirring in step S2, and the stirring speed is 110 to 130 r / min.

[0019] In a preferred embodiment, the mixture is mixed uniformly by stirring in step S2, and the stirring time is 20 to 30 seconds.

[0020] In a preferred embodiment, the mass percentage of the curing agent in the aqueous solution of the curing agent in step S3 is 30% to 40%. When the concentration of the aqueous solution of the curing agent is lower than 30%, the amount of the aqueous solution is appropriately increased; when the concentration of the aqueous solution of the curing agent is higher than 40%, the amount of the aqueous solution is appropriately reduced; it is sufficient to ensure that the mass of the curing agent accounts for 12% to 15% of the mass of the phenolic resin.

[0021] In a preferred embodiment, the mixture is mixed uniformly by stirring in step S3, and the stirring speed is 110 to 130 r / min.

[0022] In a preferred embodiment, the mixture is mixed uniformly by stirring in step S3, and the stirring time is 30 to 35 seconds.

[0023] In a preferred embodiment, the mixture is mixed uniformly by stirring in step S4, and the stirring speed is 75 to 85 r / min.

[0024] In a preferred embodiment, the mixture is mixed uniformly by stirring in step S4, and the stirring time is 15 to 25 seconds.

[0025] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: (1) In the present invention, silica sand and anhydrous borax are used as aggregates, phenolic resin is coated on the surface of the aggregate and solidified, and then boric acid is coated on the outermost layer of the coated sand, thereby obtaining coated sand with excellent heat resistance. During pouring, a large amount of latent heat will be released during the solidification process of the molten metal. After the phenolic resin is completely decomposed by heat, the anhydrous borax as one of the components of the aggregate and the boric acid coated on the surface of the sand particles begin to work. When the temperature of the sand core reaches 750±50°C, the main chemical component SiO2 of the sand particles melts and sinters under the joint action of the two, forming a dense glass layer on the surface of the sand core, which continues to resist the invasion of the molten metal into the sand core, continues to maintain the size structure of the sand core, and avoids sand sticking to the casting. (2) Boron element can shorten the melting time of SiO2, form a vitrified layer as soon as possible, and can also inhibit the thermal expansion of the glass layer, improve the strength of the glass layer, maintain the outline of the sand core, and thus avoid the size deformation of the casting. (3) In the present invention, the boric acid is distributed in the outermost layer of the coated sand, which has a lubricating effect and improves the fluidity of the coated sand, which is beneficial to the filling capacity of the coated sand in the mold. Compared with conventional coated sand, it also saves the manufacturing cost of the coated sand because no additional lubricant is needed. (4) The heat-resistant coated sand provided by the present invention is suitable for the production of large-scale cast iron and steel parts with complex structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the heat-resistant coated sand provided in the present invention.

[0027] In the figure: 1. Silica sand and anhydrous borax aggregates; 2. Phenolic resin; 3. Curing agent layer; 4. Boric acid layer. DETAILED DESCRIPTION

[0028] The following content is combined with the embodiments to clearly and completely describe the technical solution of the present application so that those skilled in the art can fully understand the present application. Obviously, the described embodiments are only some preferred embodiments of the present application, rather than all embodiments. Any equivalent transformation or substitution made to the following implementation modes by those of ordinary skill in the art without creative work belongs to the protection scope of the present application.

[0029] The phenolic resin used in the embodiments of the present application is a phenolic resin commonly used in the market for preparing coated sand. Combined with the sieve number requirements in GB / T 9442-2024 "Silica Sand for Casting", the sieve numbers of the relevant materials of the present application are selected from the following ranges: the sieve number of silica sand is 20-270 mesh; the sieve number of anhydrous borax is 20-270 mesh; the sieve number of boric acid is 300-500 mesh.

[0030] Example 1

[0031] A heat-resistant coated sand is composed of the following components: silica sand, anhydrous borax, boric acid, phenolic resin and curing agent. The mass ratio of silica sand, anhydrous borax and boric acid is 84:15.7:0.3, the silica sand is composed of three particle sizes of 50 mesh, 70 mesh and 100 mesh, the sieve number of anhydrous borax is 70 mesh, and the sieve number of boric acid is 400 mesh; the mass of phenolic resin accounts for 3% of the mass of silica sand; the mass of curing agent accounts for 13% of the mass of phenolic resin, and the curing agent is urotropine. The sieve number of anhydrous borax is the same as that of some silica sand, and there are more contact points between sand particles, so that anhydrous borax and silica sand can contact more effectively, thus having a better effect on preventing SiO2 phase change expansion.

[0032] The preparation method of the heat-resistant coated sand comprises the following steps:

[0033] S1. Fully mix silica sand and anhydrous borax according to a certain proportion to obtain a mixture A; and heat the mixture A to 150°C.

[0034] S2. Put the heated mixture A into a roller sand mixer, then add phenolic resin, control the rotation speed to 120r / min, and stir for 25s; use the heat of the mixture A to melt the phenolic resin, so that its fluidity becomes better, so that the phenolic resin is evenly coated on the surface of the silica sand particles.

[0035] S3, adding an aqueous solution of a curing agent (the mass percentage of hexamethylenetetramine in the aqueous solution of the curing agent is 35%) to the product of step S2, controlling the rotation speed to 120 r / min, stirring for 33 s, so that the water in the aqueous solution of the curing agent is fully evaporated.

[0036] S4, add boric acid to the product of step S3, control the rotation speed to 80r / min, stir for 20s, so that the boric acid is evenly distributed on the outermost layer of the coated sand, and obtain heat-resistant coated sand, whose structure is as follows Figure 1 As shown, from the inside to the outside, it is composed of silica sand and anhydrous borax aggregate 1, phenolic resin 2, curing agent layer 3 and boric acid layer 4. The finished heat-resistant coated sand is sealed and stored in a plastic film inner bag.

[0037] Example 2

[0038] A heat-resistant coated sand is composed of the following components: silica sand, anhydrous borax, boric acid, phenolic resin and curing agent. The mass ratio of silica sand, anhydrous borax and boric acid is 80:10:0.1, the silica sand is composed of components with three particle sizes of 20 mesh, 30 mesh and 40 mesh, the anhydrous borax is composed of components with two particle sizes of 20 mesh and 30 mesh, the sieve number of boric acid is 300 mesh; the mass of phenolic resin accounts for 2% of the mass of silica sand; the mass of curing agent accounts for 12% of the mass of phenolic resin, and the curing agent is hexamethylenetetramine.

[0039] The preparation method of the heat-resistant coated sand comprises the following steps:

[0040] S1. Fully mix silica sand and anhydrous borax according to a certain proportion to obtain a mixture A; and heat the mixture A to 140°C.

[0041] S2. Put the heated mixture A into a roller sand mixer, then add phenolic resin, control the rotation speed to 110r / min, and stir for 20s; use the heat of the mixture A to melt the phenolic resin, so that its fluidity becomes better, so that the phenolic resin is evenly coated on the surface of the silica sand particles.

[0042] S3, adding an aqueous solution of a curing agent (the mass percentage of hexamethylenetetramine in the aqueous solution of the curing agent is 30%) to the product of step S2, controlling the rotation speed to 110 r / min, stirring for 35 seconds, so that the water in the aqueous solution of the curing agent is fully evaporated.

[0043] S4, add boric acid to the product of step S3, control the rotation speed to 75r / min, stir for 25s, so that the boric acid is evenly distributed on the outermost layer of the coated sand, and obtain heat-resistant coated sand, whose structure is as follows Figure 1 As shown, from the inside to the outside, it is composed of silica sand and anhydrous borax aggregate 1, phenolic resin 2, curing agent layer 3 and boric acid layer 4. The finished heat-resistant coated sand is sealed and stored in a plastic film inner bag.

[0044] Example 3

[0045] A heat-resistant coated sand is composed of the following components: silica sand, anhydrous borax, boric acid, phenolic resin and curing agent. The mass ratio of silica sand, anhydrous borax and boric acid is 90:20:0.5, the silica sand is composed of components with three particle sizes of 140 mesh, 200 mesh and 270 mesh, the anhydrous borax is composed of components with two particle sizes of 200 mesh and 270 mesh, the sieve number of boric acid is 500 mesh; the mass of phenolic resin accounts for 4% of the mass of silica sand; the mass of curing agent accounts for 15% of the mass of phenolic resin, and the curing agent is urotropine.

[0046] The preparation method of the heat-resistant coated sand comprises the following steps:

[0047] S1. Fully mix silica sand and anhydrous borax according to a certain proportion to obtain a mixture A; and heat the mixture A to 160°C.

[0048] S2. Put the heated mixture A into a roller sand mixer, then add phenolic resin, control the rotation speed to 130r / min, and stir for 30s; use the heat of the mixture A to melt the phenolic resin, so that its fluidity becomes better, so that the phenolic resin is evenly coated on the surface of the silica sand particles.

[0049] S3, adding an aqueous solution of a curing agent (the mass percentage of hexamethylenetetramine in the aqueous solution of the curing agent is 40%) to the product of step S2, controlling the rotation speed to 130 r / min, stirring for 30 s, so that the water in the aqueous solution of the curing agent is fully evaporated.

[0050] S4, add boric acid to the product of step S3, control the rotation speed to 85r / min, stir for 15s, so that the boric acid is evenly distributed on the outermost layer of the coated sand, and obtain heat-resistant coated sand, whose structure is as follows Figure 1 As shown, from the inside to the outside, it is composed of silica sand and anhydrous borax aggregate 1, phenolic resin 2, curing agent layer 3 and boric acid layer 4. The finished heat-resistant coated sand is sealed and stored in a plastic film inner bag.

[0051] Example 4

[0052] A heat-resistant coated sand is composed of the following components: silica sand, anhydrous borax, boric acid, phenolic resin and curing agent. The mass ratio of silica sand, anhydrous borax and boric acid is 80:20:0.5, the silica sand is composed of components with three particle sizes of 70 mesh, 100 mesh and 140 mesh, the sieve number of anhydrous borax is 100 mesh, and the sieve number of boric acid is 325 mesh; the mass of phenolic resin accounts for 2.5% of the mass of silica sand; the mass of curing agent accounts for 12.5% ​​of the mass of phenolic resin, and the curing agent is urotropine.

[0053] The preparation method of the heat-resistant coated sand comprises the following steps:

[0054] S1. Fully mix silica sand and anhydrous borax according to a certain proportion to obtain a mixture A; and heat the mixture A to 155°C.

[0055] S2. Put the heated mixture A into a roller sand mixer, then add phenolic resin, control the rotation speed to 125r / min, and stir for 30s; use the heat of the mixture A to melt the phenolic resin, so that its fluidity becomes better, so that the phenolic resin is evenly coated on the surface of the silica sand particles.

[0056] S3. Add an aqueous solution of a curing agent (the mass percentage of hexamethylenetetramine in the aqueous solution of the curing agent is 38%) to the product of step S2, control the rotation speed to 115 r / min, and stir for 30 seconds to fully evaporate the water in the aqueous solution of the curing agent.

[0057] S4, add boric acid to the product of step S3, control the rotation speed to 80r / min, stir for 18s, so that the boric acid is evenly distributed on the outermost layer of the coated sand, and obtain heat-resistant coated sand, whose structure is as follows Figure 1 As shown, from the inside to the outside, it is composed of silica sand and anhydrous borax aggregate 1, phenolic resin 2, curing agent layer 3 and boric acid layer 4. The finished heat-resistant coated sand is sealed and stored in a plastic film inner bag.

[0058] Example 5

[0059] A heat-resistant coated sand is composed of the following components: silica sand, anhydrous borax, boric acid, phenolic resin and curing agent. The mass ratio of silica sand, anhydrous borax and boric acid is 90:10:0.1, the silica sand is composed of three particle sizes of 100 mesh, 140 mesh and 200 mesh, the sieve number of anhydrous borax is 140 mesh, and the sieve number of boric acid is 400 mesh; the mass of phenolic resin accounts for 4% of the mass of silica sand; the mass of curing agent accounts for 14% of the mass of phenolic resin, and the curing agent is urotropine.

[0060] The preparation method of the heat-resistant coated sand comprises the following steps:

[0061] S1. Fully mix silica sand and anhydrous borax according to a certain proportion to obtain a mixture A; and heat the mixture A to 145°C.

[0062] S2. Put the heated mixture A into a roller sand mixer, then add phenolic resin, control the rotation speed to 130r / min, and stir for 25s; use the heat of the mixture A to melt the phenolic resin, so that its fluidity becomes better, so that the phenolic resin is evenly coated on the surface of the silica sand particles.

[0063] S3, adding an aqueous solution of a curing agent (the mass percentage of hexamethylenetetramine in the aqueous solution of the curing agent is 32%) to the product of step S2, controlling the rotation speed to 130 r / min, stirring for 35 seconds, so that the water in the aqueous solution of the curing agent is fully evaporated.

[0064] S4, add boric acid to the product of step S3, control the rotation speed to 82r / min, stir for 16s, so that the boric acid is evenly distributed on the outermost layer of the coated sand, and obtain heat-resistant coated sand, whose structure is as follows Figure 1 As shown, from the inside to the outside, it is composed of silica sand and anhydrous borax aggregate 1, phenolic resin 2, curing agent layer 3 and boric acid layer 4. The finished heat-resistant coated sand is sealed and stored in a plastic film inner bag.

[0065] Comparative Example 1

[0066] A coated sand is composed of the following components: silica sand, anhydrous borax, phenolic resin and curing agent. The mass ratio of silica sand to anhydrous borax is 84.0:16.0, the silica sand is composed of components with three particle sizes of 50 mesh, 70 mesh and 100 mesh, the sieve number of anhydrous borax is 70 mesh; the mass of phenolic resin accounts for 3% of the mass of silica sand; the mass of curing agent accounts for 13% of the mass of phenolic resin, and the curing agent is urotropine.

[0067] The method for preparing the coated sand is basically the same as that in Example 1, except that there is no step S4, and the coated sand is obtained after the water in step S3 is completely evaporated.

[0068] Comparative Example 2

[0069] A coated sand is composed of the following components: silica sand, boric acid, phenolic resin and curing agent. The mass ratio of silica sand to boric acid is 84.0:16.0, the silica sand is composed of components with three particle sizes of 50 mesh, 70 mesh and 100 mesh, the sieve number of boric acid is 400 mesh; the mass of phenolic resin accounts for 3% of the mass of silica sand; the mass of curing agent accounts for 13% of the mass of phenolic resin, and the curing agent is hexamethylenetetramine.

[0070] The method for preparing the coated sand is substantially the same as that in Example 1, except that in step S1, the silica sand is directly heated to 150° C., and in step S2, the heated silica sand is put into a roller-type sand mixer.

[0071] Comparative Example 3

[0072] This comparative example provides a coated sand, the composition of which is the same as that of the heat-resistant coated sand in Example 1; the difference is that the preparation method of the coated sand comprises the following steps:

[0073] P1. Fully mix silica sand, anhydrous borax and boric acid according to a certain proportion to obtain a mixture B; heat the mixture B to 150°C.

[0074] P2. Put the heated mixture B into a roller sand mixer, then add phenolic resin, control the speed to 120r / min, and stir for 25s; use the heat of mixture B to melt the phenolic resin, making its fluidity better, so that the phenolic resin is evenly coated on the surface of the silica sand particles.

[0075] P3. Add an aqueous solution of a curing agent (the mass percentage of hexamethylenetetramine in the aqueous solution of the curing agent is 35%) to the product of step P2, control the rotation speed to 120 r / min, stir for 33 seconds, and allow the water in the aqueous solution of the curing agent to fully evaporate to obtain coated sand.

[0076] Coated sand performance test

[0077] Under the condition of the same resin amount, according to the provisions of JB / T 8583-2008 "Coated Sand for Foundry", the properties of the coated sand in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1.

[0078] Table 1 Test results of coated sand performance

[0079]

[0080]

[0081] The composition of conventional coated sand in Table 1 is as follows: 100 parts of silica sand, 2 parts of phenolic resin, 0.3 parts of curing agent hexamethylenetetramine, and 0.5 parts of lubricant calcium stearate.

[0082] The sintering rate test method is as follows: Take 50g of coated sand sample, accurately weigh the mass, record it as M0, and place it in a corundum crucible. Place the corundum crucible in a high-temperature furnace at 1000℃ and bake it for 10 minutes. Take out the corundum crucible and cool it to room temperature. The unsintered sand particles will fall off automatically. Weigh the mass of the sintered sand block and record it as M1. Sintering rate The larger the value, the better the sintering property of the coated sand.

[0083] As can be seen from Table 1, the sintering performance of the coated sand prepared by the present invention is significantly better than that of conventional coated sand and the coated sand in Comparative Examples 1 to 3. The coated sand of Comparative Example 1 does not add boric acid and lubricant calcium stearate, the melting point of the coated sand is significantly reduced, it is very easy to agglomerate in a high temperature and high humidity environment, and the sintering rate is significantly reduced. This is because anhydrous borax is dispersed in silica sand in a granular form, and boric acid is evenly coated on the surface of each grain of sand, which has a more significant fluxing effect. The coated sand of Comparative Example 2 does not add anhydrous borax. When the temperature reaches 573°C (lower than the melting temperature of SiO2 750±50°C), the expansion force generated by the phase change expansion of SiO2 makes it difficult for the sand particles to blend together, and the sintering rate is significantly low; in addition, because a large amount of boric acid is covered on the surface of the sand particles, the reaction of the binder phenolic resin and the curing agent urotropine between the sand particles is prevented, and cross-linking and curing are difficult, resulting in a significantly high melting point and a significantly reduced strength. In comparative example 3, silica sand, boric acid and anhydrous borax are mixed in advance when preparing coated sand. Boric acid will coat the surface of silica sand. Boric acid is acidic and phenolic resin is alkaline, and they will react with each other, resulting in extremely low strength. In addition, because the strength of coated sand is extremely low (refractory is also low), the phenolic resin on the surface of sand grains cannot withstand the temperature of 700-800°C, so it loses structural strength and collapses prematurely, resulting in an extremely low sintering rate.

[0084] The above-described embodiments are only preferred embodiments of the present application and are not intended to limit the scope of protection of the present application. For any person skilled in the art, the present application may have various changes and modifications. Any simple equivalent changes and modifications made based on the scope of protection of the present application and the contents of the specification should be included in the scope of protection of the present application.

Claims

1. A heat-resistant coated sand, characterized in that: The invention is composed of silica sand, anhydrous borax, boric acid, phenolic resin and curing agent; the mass ratio of the silica sand, the anhydrous borax and the boric acid is (80-90):(10-20):(0.1-0.5), the mass of the phenolic resin accounts for 2%-4% of the mass of the silica sand; the mass of the curing agent accounts for 12%-15% of the mass of the phenolic resin.

2. The heat-resistant coated sand according to claim 1, characterized in that: The mass ratio of the silica sand, the anhydrous borax and the boric acid is 84:15.7:0.

3.

3. The heat-resistant coated sand according to claim 1, characterized in that: The sieve number of the silica sand is 20-270 meshes; or / and the sieve number of the anhydrous borax is 20-270 meshes; or / and the sieve number of the boric acid is 300-500 meshes.

4. The heat-resistant coated sand according to claim 1, characterized in that: The curing agent is hexamethylenetetramine.

5. The method for preparing heat-resistant coated sand according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mixing silica sand and anhydrous borax in proportion to obtain a mixture A; heating the mixture A; S2, adding phenolic resin to the heated mixture A and mixing well; S3, adding an aqueous solution of a curing agent to the product of step S2 and mixing evenly; S4. Add boric acid to the product of step S3 and mix well to obtain the heat-resistant coated sand.

6. The preparation method according to claim 5, characterized in that: In step S1, the mixture A is heated to 140-160°C.

7. The preparation method according to claim 5, characterized in that: In step S2, the mixture is mixed uniformly by stirring at a speed of 110 to 130 r / min; or / and the stirring time is 20 to 30 s.

8. The preparation method according to claim 5, characterized in that: The mass percentage of the curing agent in the aqueous solution of the curing agent in step S3 is 30% to 40%.

9. The preparation method according to claim 5, characterized in that: In step S3, the mixture is mixed uniformly by stirring at a speed of 110 to 130 r / min; or / and the stirring time is 30 to 35 s.

10. The preparation method according to claim 5, characterized in that: In step S4, the mixture is mixed uniformly by stirring at a speed of 75 to 85 r / min; or / and the stirring time is 15 to 25 s.